Redevelopment North Sumatera Culture - Andalucia .; Miftah Fauzan Putra (Talenta Publisher, 2017)
The field should have a representative and iconic place for the value of art. Representative and iconic became a common point of view of the community so easily recognized and emerging interest to try the various activities in it. However, the state of today's cultural park is not feasible to accommodate local art and cultural activities. Such inadequacy is evidenced by the decline of public interest. Therefore, it is necessary to rejuvenate the North Sumatra Cultural Park to function again as a forum capable of responding to the community's response to art and culture. North Sumatra Redevelopment expected to perform its function optimally as an art development of Medan city.